Responding to the first era of globalization: Canadian trade policy, 1870-1913 - Patrick Alexander; Ian Keay (Bank of Canada, 2018)
In this paper we document Canada's trade policy response to late-nineteenth- and earlytwentieth-century globalization. We link newly digitized annual product-specific data on the value of Canadian imports and duties paid from 1870-1913 to establishment-specific production and location information drawn from the manuscripts of the 1871 industrial census. Our findings reveal a highly selective move towards protectionism following the adoption of the National Policy in 1879. Changes in the Canadian tariff schedule narrowly targeted final consumption goods that had close substitutes produced by relatively large, politically influential domestic manufacturers.
Keywords: F; F1; F13; F14; F42; F60; N; N71; 330; Trade integration; Economic models; International topics